Economic Imperatives for Women's Writing in Early Modern Europe (Volume 2) - Font Paz, Carme; Geerdink, Nina (Brill, 2018)
Economic Imperatives for Women's Writing in Early Modern Europe delves into the early modern history of women's authorship and literary production in Europe taking a material turn. The case studies included in the volume represent women writers from various European countries and comparatively reflect the nuances of their participation in a burgeoning commercial market for authors while profiting as much from patronage. From self-representation as professional writers to literary reception, the challenges of reputation, financial hardships, and relationships with editors and colleagues, the essays in this collection show from different theoretical standpoints and linguistic areas that gender biases played a far less limiting role in women's literary writing than is commonly assumed, while they determined the relationship between moneymaking, self-representation, and publishing strategies.